(untitled) - Randall, Mick (Cambridge, UK, 2001)
Advising and Supporting Teachers examines the role of the teacher-advisor and how the key skills required for producing effective feedback can be developed. The book is in two parts. The first part looks at the processes of giving advice and the second part consists of a range of tasks for the advisor. The main purpose of this book is to provide an opportunity for those involved in providing feedback to reflect on the methods which can be used to maximise the effectiveness of the learning encounter. This book will be of particular interest to everyone responsible for advising teachers including teaching practice supervisors, mentors, INSET tutors, state education inspectors, Directors of Studies running teacher appraisal and induction programmes and teachers working together as 'critical friends' in informal teacher development.
Keywords: English language,English teachers; Study and teaching,Foreign speakers,Training of